We who are dark : the philosophical foundations of Black solidarity / Tommie Shelby. - Shelby, Tommie, 1967- (Belknap Press of Harvard University Press, 2005)
We Who Are Dark provides the first extended philosophical defense of black political solidarity. Tommie Shelby argues that we can reject a biological idea of race and agree with many criticisms of identity politics yet still view black political solidarity as a needed emancipatory tool. In developing his defense of black solidarity, he draws on the history of black political thought, focusing on the canonical figures of Martin R. Delany and W.E.B. Du Bois.